Mathematical Modeling of Microwave Drying Kinetics of Ginger (Zingiber officinale) Slices - Kumar, Ashok; Kulkarni, Neha; Kedarnath, (Journal of Postharvest Technology, 2014)
In this work, the microwave drying behaviour of ginger was  investigated. The constant rate period is absent from the drying  curves. The drying process took place in the falling rate period.  The drying data were fitted to five mathematical models namely,  Exponential, Page, Henderson and Pabis, Logarithmic and Power  law models and validated on the basis of determination of  coefficient (R2), reduced mean square (χ2) of the deviation, mean  bias error (EMB) and root mean square error (ERMS) between the  observed and predicted values of moisture ratios. Page model was  found to fit best, representing an excellent tool for estimation of  the drying time and the values of R2, χ², ERMS and EMB were in the  ranged of 0.995 to 0.997; 0.0006 to 0.005; 0.022 to 0.038 and  0.005 to 0.009 respectively. The effective diffusivity coefficient of  moisture transfer from ginger was found within the range of  2.5356 × 10-11 to 1.2678 × 10-9 m2 s-1.
Keywords: Ginger; Falling rate; Mathematical modeling Diffusivity; Drying time